Behaviour of Expansive Soils Stabilized with Hydrated Lime and Bagasse Fibres. (2016) - Dang, Liet Chi; Fatahi, Behzad; Khabbaz, Hadi
Abstract: Soil stabilization is the most common ground improvement technique adopted to improve problematic soil properties. This investigation exhibits a series of laboratory tests conducted to evaluate the influences of bagasse fibres and hydrated lime addition on the engineering properties and shrink-swell behaviour of stabilised expansive soils. Bagasse fibre is industrial waste by-product left after the crushing of sugar cane for juice extraction that was used in this study as reinforcing component for expansive soil stabilization. The expansive soils used in this investigation were collected from Queensland, Australia. In order to investigate the influences of bagasse fibres on the engineering behaviour of expansive soil, varying proportions of randomly distributed bagasse fibres of 0.5%, 1.0%, and 2.0% were added to expansive soil and hydrated lime-expansive soils mixed with different bagasse fibre proportions were also investigated. Although, an array of experimental tests have been undertaken on untreated and treated expansive soil samples, merely the outcomes of linear shrinkage, unconfined compressive strength (UCS) tests after various curing periods of 3, 7 and 28 days are presented in this paper. Other test results have been identified as follow up research. The findings of this experimental investigation indicate that bagasse fibre reinforcement blended with hydrated lime increased the compressive strength of expansive soil with increase in curing time and additives contents, whereas the linear shrinkage of stabilised expansive soils decreased with increasing hydrated lime and bagasse fibre proportions and curing periods. Based on the reasonable laboratory test results, it can be noted that the expansive soils can be successfully stabilized by combination of hydrated lime and bagasse fibres.